2000
DOI: 10.1007/s002770000166
|View full text |Cite
|
Sign up to set email alerts
|

Sjögren's syndrome associated with multiple myeloma

Abstract: Sjögren's syndrome (SS) is a chronic autoimmune disease of unknown etiology characterized by lymphocytic infiltration of the exocrine glands and a polyclonal B-cell activation; it is demonstrated by the presence of multiple autoantibodies against organ- and non-organ-specific autoantigens. SS is associated with malignant lymphomas, Waldenstrom's macroglobulinemia and benign monoclonal gammopathy, while its relationship with multiple myeloma is extremely rare. The association between multiple myeloma and rheuma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0
8

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 0 publications
1
15
0
8
Order By: Relevance
“…BJ proteinuria was not included in the diagnostic criteria for the following issues. Firstly, as reported by others 27 and also in our experience, Globulin (g dl -1 ) 9 1 0 1 1 8.5 9 9.5 10 10.5 Total protein (g dl -1 ) 11 11.5 12 12.5 Figure 3. The data refer to case 1: Graph ics represent the best fitted exponential curve between serum viscocity (SV) and total protein, globulin and M-component.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…BJ proteinuria was not included in the diagnostic criteria for the following issues. Firstly, as reported by others 27 and also in our experience, Globulin (g dl -1 ) 9 1 0 1 1 8.5 9 9.5 10 10.5 Total protein (g dl -1 ) 11 11.5 12 12.5 Figure 3. The data refer to case 1: Graph ics represent the best fitted exponential curve between serum viscocity (SV) and total protein, globulin and M-component.…”
Section: Discussionsupporting
confidence: 70%
“…10 The monoclonal component may also cause, as a consequence of autoantibody activity, immune mediated phenomena, such as cryoglobulinemia peripheral neuropathies and cold agglutinin haemolytic anaemia. 3,11,12 Common laboratory findings both in humans and dogs are anaemia, leukocytosis/leukopenia, pancytopenia, hypergammaglobulinemia of IgM type, cryoglobulinemia and Bence-Jones (BJ) proteinuria. 3,13,14 Possible secondary reported complications associated with WM include a second neoplasm, infection (sepsis) and progressive renal insufficiency.…”
Section: Introductionmentioning
confidence: 99%
“…The association between pSS and MM has been suggested in case reports 2830. The hypothesis was based on the observation that many patients with pSS had benign monoclonal gammopathy, and the association between benign monoclonal gammopathy and MM was well established.…”
Section: Discussionmentioning
confidence: 99%
“…Wada et al [9] reported a case of MM complicated by autoimmune hemolytic anemia. Terpos et al [10] also reported a case of MM developing SS. However, these case reports could not show a true association between disease activity of MM and subsequent autoimmune disorders.…”
Section: Discussionmentioning
confidence: 92%